2019
DOI: 10.2147/ott.s220453
|View full text |Cite
|
Sign up to set email alerts
|

<p><em>Camellia nitidissima</em> Chi Extract Potentiates the Sensitivity of Gastric Cancer Cells to Paclitaxel via the Induction of Autophagy and Apoptosis</p>

Abstract: Background: Camellia nitidissima Chi (CNC) has been applied as a traditional folk medicine for the effective treatment of various diseases. However, there is little research regarding the mechanism of CNC on pharmaceutical function including anticancer effect. Materials and methods: JHC-4 is a n-butanol extract from CNC. The anti-proliferation effect was evaluated by MTT assays. Monodansylcadaverine (MDC) staining, Western blotting and autophagy inhibitors (CQ and BafA1) were applied to determine whether JHC-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…As a plant with both medicinal and ornamental value, the pharmacological effects of its flower fractions have been thoroughly studied ( 34 , 36 , 37 ), while the research on leave fractions was rare. Furthermore, few studies have systematically investigated the differences in the chemical composition of the four active fractions of CNC.…”
Section: Discussionmentioning
confidence: 99%
“…As a plant with both medicinal and ornamental value, the pharmacological effects of its flower fractions have been thoroughly studied ( 34 , 36 , 37 ), while the research on leave fractions was rare. Furthermore, few studies have systematically investigated the differences in the chemical composition of the four active fractions of CNC.…”
Section: Discussionmentioning
confidence: 99%
“…CNC is a TCM with a medicinal history of more than 2000 years. Modern pharmacological studies have suggested that CNC has a wide range of anti-tumor properties ( 26 , 27 ), in liver cancer, lung cancer, esophageal cancer, and others. Here we studied the anti-colon cancer efficacy of CNC in vivo and in vitro to explore potential mechanisms underlying these effects.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagic morphological changes were evaluated by fluorescence microscopy using monodansylcadaverine (MDC) staining. MDC is a specific marker for autophagosome formation [ 34 ]. After the indicated treatments, cells were rinsed with PBS for 3 times and incubated in 200 µl of 0.05 mM MDC (Solarbio, Beijing, China) at 37 °C for 30 min.…”
Section: Methodsmentioning
confidence: 99%